Nitrogen cycling in Laguna Madre and Baffin Bay - An, Soonmo, 1964-; Gardner, Wayne Stanley, 1941- (2000)
Estuarine phytoplankton production can be limited by N availability (Ryther & Dunstan 1971, Hecky & Kilham 1988) and sediments often serve as an important source of dissolved inorganic N . . Denitrification is the only biological process that transforms combined N to gaseous forms . . These gaseous end-products represent unavailable nutrient sources to most estuarine producers (e.g., phytoplankton and bacteria; Howarth et al. 1988). Benthic denitrification has proven to be a significant sink for combined N in systems where detailed studies of denitrification have been completed. This process may drive systems toward N limitation (Seitzinger 1990). The purposes of this study were to evaluate the importance of denitrification in nitrogen cycling and to examine environmental conditions influencing nitrogen cycling in Laguna Madre and Baffin Bay. A membrane inlet mass spectrometer (MIMS) system for dissolved gas measurement and a high performance liquid chromatography (HPLC) system for ammonium isotope measurement, that are available at the University of Texas Marine Science Institute, allowed us to measure dissimilatory nitrate reduction to ammonium (DNRA) as another major nitrate reduction pathway in addition to denitrification. Submitted to: The Texas Water Development Board, contract no. 99-483-278 July 2000 Marine Science